Design and Development Automatic Fish Feed Measuring and Feeding System Based on Internet of Things - Wijaya, Komang Martadana; Piarsa, I Nyoman; Wira Buana, Putu (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi); Vol 11 No 2 (2023): Vol. 11, No. 2, August 2023DO - 10.24843/JIM.2023.v11.i02.p06, 2023)
This research aims to design and implement an IoT-based automated fish feeding and dosing system to improve the efficiency of the feeding process through automation. The components used include the ESP32 microcontroller, RTC sensor, ultrasonic sensor, voltage sensor, stepper motor, LCD, DC motor, and relay. The system performs dosing and feeding based on user-defined schedules. Based on the research results, the system successfully monitors and controls the dosing and feeding process of the fish automatically. However, the overall success rate of the system is only 70%, with an average error rate of 1.36% for the voltage sensor and 1.33% for the ultrasonic sensor. The battery experiences an average hourly decrease of 0.19V during system operation. The system faced challenges such as relying on Wi-Fi connection to connect to the Firebase server, insufficient battery capacity, and the unreliability of the stepper motor for dosing purposes.